HUBUNGAN SISTEM KEARSIPAN DENGAN KEPUASAN PELAYANAN ADMINISTRASI PASIEN - Nadila Agustina; Muhammad Aditya Rachman (Nusadaya Journal of Multidiciplinary Studies, 2026)
A filing system is a crucial component in supporting the quality of patient administration services in healthcare facilities. Proper archive management enables the recording, storage, and retrieval of patient data to be carried out quickly, accurately, and efficiently. This study aims to analyze the relationship between a filing system and patient satisfaction with administrative services. A quantitative analysis approach was used, examining various aspects of archiving, such as speed of data access, information accuracy, and document security. The results indicate that an effective filing system positively impacts patient satisfaction, particularly in terms of service time, data accuracy, and ease of administrative processes. Conversely, a disorganized filing system can lead to service delays, data errors, and reduced patient trust. Therefore, it can be concluded that improving the quality of the filing system is a crucial factor in enhancing patient satisfaction with administrative services. Therefore, standardized and technology-based archive management is needed to support more optimal services.